(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study examines the challenges facing urban heritage, represented by human factors such as urbanization, urban expansion, neglect, conflicts and wars, and natural factors such as earthquakes and floods, with an analysis focusing on the old Rusafa area in Baghdad, which is rich in cultural heritage and currently suffers from many dangers. The challenge lies in confronting these risks and preserving heritage. This research provides a comprehensive exploration of the key influences, methodologies, results, and conclusions related to the preservation of the cultural heritage of the ancient region amidst these challenges. Drawing on a mixed-methods approach that includes expert surveys, thematic analysis, and case studies, this study identifies a consensus among scholars and practitioners about the risks posed by current challenges to cultural heritage. Despite the diversity of opinions regarding the entry of digital technology into the field of heritage, there is now a strong consensus regarding the use of digital technologies in documenting cultural heritage, and the main results indicate that heritage is one of the fields that has had a noticeable benefit in digital transformation, and to ensure the long-term sustainability of heritage without being exposed to various factors, documentation is the first step in protecting urban heritage using various techniques. A database is created as a result of the documentation process, which is the basic stage in the protection and dissemination of final information in the media for tourism, with the possibility of collaboration between the public and private sectors to conduct documentation. He emphasizes research on the role of technology in diagnosing and recording heritage to preserve it, enjoy it, and pass it on to current and future generations